Precautionary Measures, Attitude, and Productive Activities of Students in West Java Province, Indonesia, during Covid-19 Pandemic - Rimadani Pratiwi; Intan T. Maisyarah; Nyi M. Saptarini (Jurnal Farmasi Klinik Indonesia, 2022)
The Covid-19 pandemic has been ongoing for approximately one year, hence, several activities must be carried out remotely from home. Studying from home for every level of education has its challenges, specifically for university students in terms of maintaining productive activity. Therefore, this study aimed to determine the impact of a one-year pandemic on the precautionary measures, attitudes, and productive activities of students in Indonesia. A descriptive cross-sectional approach was used, and an online questionnaire was distributed between 11–15 January 2021 to 628 undergraduates in West Java Province. The result showed that students still adhere to health protocols by wearing a face mask (93.8%), washing hands (74.7%), and social distancing (64.5%), but they were feeling bored (60.2%) with the online activities carried out at home. A total of 81.4% hope the activity and online class can change to face-to-face to keep social interaction with other people. In productivity, more than 40% can find new hobbies and carry out positive activities while staying at home. They were also feeling more grateful during the pandemic. Based on the results, students are still aware of health protocols and regulations of the government as precautionary measures for the spread of Covid-19. Despite the boredom, they can still stay productive by engaging in positive activities at home.Keywords: Attitude, Covid-19, online activity, precautionary measures, productivity Tindakan Pencegahan, Sikap, dan Aktivitas Produktif Mahasiswa di Provinsi Jawa Barat, Indonesia, selama Pandemi Covid-19AbstrakPandemi Covid-19 sudah berlangsung kurang lebih satu tahun, dan selama waktu tersebut, banyak kegiatan yang harus dilakukan dari rumah. Bagi pelajar di setiap jenjang pendidikan, termasuk mahasiswa, pembelajaran secara daring memiliki tantangan tersendiri khususnya dalam menjaga aktivitas produktif. Penelitian ini bertujuan untuk mengetahui dampak pandemi Covid-19 terhadap tindakan pencegahan, sikap, dan aktivitas produktif mahasiswa di Indonesia selama satu tahun pandemi dengan metode studi potong lintang deskriptif. Kuesioner online disebarkan pada tanggal 11–15 Januari 2021 kepada mahasiswa di Indonesia khususnya provinsi Jawa Barat, dan sebanyak 628 mahasiswa sarjana berpartisipasi sebagai responden. Hasil penelitian menunjukkan bahwa mahasiswa masih mematuhi protokol kesehatan dengan menggunakan masker (93,8%), mencuci tangan (74,7%), dan menjaga jarak (64,5%). Namun mereka merasa jenuh (60,2%) dengan aktivitas yang selalu dilakukan di rumah secara daring. Sekitar 81,4% responden berharap kegiatan dan kelas daring dapat berubah menjadi tatap muka untuk menjaga interaksi sosial dengan orang lain. Dalam aspek produktivitas, lebih dari 40% mahasiswa dapat menemukan hobi baru dan melakukan banyak kegiatan positif selama di rumah dan merasa lebih bersyukur di masa pandemi ini. Sebagai simpulan, para pelajar di Indonesia masih sadar akan protokol kesehatan dan menerapkan peraturan pemerintah tentang tindakan pencegahan penyebaran Covid-19. Meski aspek sikap mereka menunjukkan rasa jenuh, mereka dapat tetap produktif dengan melakukan kegiatan positif di rumah.Kata kunci: Aktivitas daring, Covid-19, produktivitas, sikap, tindakan pencegahan